Isolated twisted hematosalphinx misleading with ovarian cyst torsion - Khairnar, Vaibhav; Valecha, Shalini Mahana; ., Pandeeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Normal or chronically inflamed fallopian tube can undergo torsion and present as acute abdomen, simulating clinically as ectopic gestation. Torsion of the fallopian tube is less frequent but significant cause of lower abdominal pain in reproductive age women that is difficult to recognize preoperatively. Authors present a rare case of hematosalpinx with torsion at its pedicle with hemoperitonium who presented as 28 years old female with acute abdomen that was successfully treated. In cases presenting with hemoperitoneum diagnosis of ruptured ectopic pregnancy should be made unless proved otherwise during reproductive age. Rarely ruptured ovarian cyst may also be a cause. Unfortunately, hematosalpinx sometimes can undergo torsion due to circulatory imbalance and can present as hemoperitoneum and circulatory collapse due to rupture. There have been no specific symptoms, clinical findings, imaging or laboratory characteristics identified for this condition. Imaging findings are non-specific in the preoperative diagnosis of torsed fallopian tubes. Therefore, most of cases with isolated fallopian tubal torsion had a delayed diagnosis and a subsequent delay of timely intervention that may result in failure to save tubal function. Torsion of tube can lead to hematosalpinx, hemoperitonium and necrosis of tube which necessitates urgent surgical management. This case report describes a twisted hematosalpinx presentation without any predisposing high-risk factors. A tubal torsion should be suspected in females with acute pelvic pain, of any age group. An early diagnosis and treatment are required to prevent complications. This rare case may highlight a new insight into pathogenesis of tubal torsion associated with hematosalpinx.